Ice storms generate spatially heterogeneous damage patterns at the watershed scale in forested landscapes. Issue 11 (20th November 2014) - Isaacs, Rachel E.; Stueve, Kirk M.; Lafon, Charles W.; Taylor, Alan H.
Abstract : The effects of large‐scale disturbances play a pivotal role in shaping ecosystem structure and function. Interactions between disturbances and a multitude of biophysical factors at different scales generate spatially heterogeneous patterns of damage on vegetated landscapes. However, research on large‐scale disturbances is often conducted at one spatial extent because of the challenges associated with quantifying patterns of damage in vegetation across multiple spatial extents. Consequently, the literature has identified many different and often conflicting biophysical controls of vegetation damage, which is likely a consequence of the historical and spatial contingency of particular geographic locations. We investigated the influence of biophysical factors and spatial extent of ice storm damage patterns across the entire Ouachita National Forest and in 65 individual watersheds. This allowed for an assessment of how spatial extent and contingency might influence statistical results and therefore any conclusions drawn from these analyses. Two pre‐ and post‐storm Landsat 7 ETM+ scenes (October 6, 1999 and September 25, 2001) were acquired to map ice storm damage based on the normalized difference vegetation index (NDVI) change. Field sites verified the relationship between NDVI and actual forest damage from the storms. We derived topographic variables from a digital elevation model (DEM) and biological variables from GAP‐generated data. The relationship between ice storm damage patterns and biophysical factors across the entire national forest landscape was weak. However, the relationship between damage severity, topography, and forest type increased significantly at the watershed scale, though the specific variable displaying the strongest influence varied by individual watershed. This research demonstrates that complex topography and biological factors interact with the meteorological characteristics of ice storms to generate spatially heterogeneous damage patterns in forests at the watershed scale. It is likely that the damage patterns corresponding to a particular watershed will be repeated during future disturbances.